2013
DOI: 10.1007/s12070-013-0649-3
|View full text |Cite
|
Sign up to set email alerts
|

Pre and Post Operative Voice Analysis After Medialization Thyroplasty in Cases of Unilateral Vocal Fold Paralysis

Abstract: The present study was undertaken to assess the efficacy of medialization thyroplasty on outcome of voice quality in vocal cord paralysis by analyzing the voice. A total 19 patients with vocal cord paralysis of different etiologies were included in the study. Preoperative voice analysis was done by voice recordings, GRBAS score, maximum phonation time (MPT) and acoustic analysis using Dr Speech software (University version 4.0) using habitual fundamental frequency (F0), jitter %, shimmer % and normalized noise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 15 publications
2
9
0
Order By: Relevance
“…It is of low cost, and utilizes instruments and resources which are already readily available in most ENT departments. Although not the focus of this paper, the results of the parameters tested show that this technique is effective (mean improvement in MPT 9.7 s) and comparable to previously published data on voice post standard type I thyroplasty (8)(9)(10), with no additional complications.…”
Section: Discussionsupporting
confidence: 84%
“…It is of low cost, and utilizes instruments and resources which are already readily available in most ENT departments. Although not the focus of this paper, the results of the parameters tested show that this technique is effective (mean improvement in MPT 9.7 s) and comparable to previously published data on voice post standard type I thyroplasty (8)(9)(10), with no additional complications.…”
Section: Discussionsupporting
confidence: 84%
“…However, in the present study only an increase in MPT was found in both the success and failure groups after lipoinjection laryngoplasty, while no changes were found in GRBAS. The reason may be that lipoinjection laryngoplasty improves the glottic closure efficiency, and MPT was useful to assess the improvements [ 33 ]. GRBAS is emphasized in the perceptual assessment of voice quality [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study conducted tests on different vowels and attributed dysphonia to the different supraglottal changes during [a] and [i] phonation, which, in turn, affect vocal tract resonances [ 32 ]. A dynamic magnetic resonance imaging study demonstrated the different movement of the vocal folds for [a] and [i] vowels and revealed a lower larynx position in [a] vowel production than in [i] vowel production [ 33 ]. However, differences in testing [a] and [i] persist even in the LP model, in which voicing comes directly from the vocal fold and is not affected by the actions of the vocal tract, such as the pharynx, oral cavity, and tongue.…”
Section: Discussionmentioning
confidence: 99%
“…It measures irregularity of mucosal vibration of the vocal folds that may affect the F0, jitter, shimmer and NHR. The acoustic parameters were documented in papers reporting voice improvement in unilateral vocal fold paralysis patients following surgical intervention.…”
Section: Discussionmentioning
confidence: 99%